Sistem Pengendali Dan Monitoring S1rkulasi Air Berbasis Mikrokontroler Mc68hc908kx8 - Agus Wirawan (Institute of Computer Science (IOCS), 2022)
In an industry it is often necessary to have an automatic control in every industrial process. Misainya in chemical companies. Where each industrial process requires the mixing of several chemicals in liquid form continuously all at once and in each mixing constant and controlled circulation is desired. So we want a tool that can be used to regulate the circulation of water and control it constantly and monitor the volume of liquid from the control center without having to visit each of the mixing tanks. This system uses the MC68HC908KX8 microcontroller made by Motorola included in the 8-bit processor as the central controller. The im water circulation control system consists of several controller circuits including keypad circuits, water sensor circuits, microcontroller circuits, display circuits, and driver circuits for motors and pumps. The process starts from reading the water sensor, where this sensor is in the form of a probe that is installed sequentially from the bottom to the top of the tub with a level level from 0 to 8. The output from this water sensor is fed to the microcontroller which will eventually be displayed on the water level display. In addition to reading the water level and sensor, the m.krokontroler also looks at the desired water level request according to the level selection from the selection button displayed on the button display. During the control process, the microcontroller will always see a display where the selection number will be used as a reference for the microcontroller to maintain the water level according to demand. The water level sensor system used is very good for salt water and not so good for clean water or bathroom wastewater. The size of the work area on this tool is still relatively imperfect, because the wiper motor and water pump as input output water use little power. Besides that, the water sensor used is simple and made of iron wire which corrodes easily. So it is necessary to develop the use of a motor with greater power and a water sensor that is anti-corrosion, capable of detecting and working well for any liquid. Besides that, the water sensor used is simple and made of iron wire which corrodes easily. So it is necessary to develop the use of a motor with greater power and a water sensor that is anti-corrosion, capable of detecting and working well for any liquid.